Water insecurity and sexual and gender-based violence among refugee youth: qualitative insights from a humanitarian setting in Uganda - Logie, Carmen H.; Okumu, Moses; Coelho, Madelaine; Loutet, Miranda G.; Narasimhan, Manjulaa; Lukone, Simon Odong; Kisubi, Nelson; Musoke, Daniel Kibuuka; Kyambadde, Peter; Dorea, Caetano; Taing, Lina (Journal of water, sanitation, and hygiene for development, 2022)
Refugee youth disproportionately experience sexual and gender-based violence (SGBV) and water insecurity, yet their SGBV experiences in the context of water insecurity are understudied. In this qualitative study, we conducted six focus groups (n = 48) and in-depth individual interviews (IDI) (n = 12) with refugee youth aged 16–24, and IDI with refugee elders (n = 8) in Bidi Bidi Refugee Settlement, Uganda. We applied thematic analysis informed by a social contextual framework and found that (1) SGBV is gendered, whereby adolescent girls and young women (AGYW) were targets for violence (symbolic context), and is intertwined with gender norms linked to AGYW's water collection roles (relational context); (2) water scarcity and off-site access to water infrastructure, combined with limited lighting, provide insecure environments that exacerbate AGYW's SGBV risks (material context); (3) participant generated solutions to water insecurity-related SGBV included engaging men and communities in dialogue and water collection (relational context), technology (e.g., solar lighting), improved security, and additional water points (material context). Findings signal the need to integrate water and sanitation hygiene development with SGBV prevention and sexual health (e.g., post-rape care) interventions. Refugee youth and communities should be meaningfully engaged in developing contextually relevant, gender transformative services to mitigate SGBV risks and advance health and rights.